Odpowiedzi

Najlepsza Odpowiedź!
2010-01-23T20:59:57+01:00
2010-01-23T21:14:49+01:00
Y = x²/(x -1)
x²/(x-1 ) = [x² -1 +1]/(x-1) = [x² -1]/(x-1)+ 1/(x-1) = (x+1) + 1/(x-1)
f(x) = x²/(x-1) = x+1 = 1/(x-1)
całka nieoznaczona
∫f(x)dx = ∫[ x+1 + 1/(x-1)] dx= ∫(x+1)dx + ∫ dx/(x-1) =
= (1/2)x² + x + ln Ix-1I + C
Korzystałem ze wzorów
∫(x^n)dx = [x^(n+1)]/(n+1) + C₁ , gdzie n ≠ -1 , x > 0
oraz
∫ [f¹(x) dx] /(f(x)) = ln I f(x)I + C₂
całka oznaczona w granicach całkowania od a do b :
b
∫f(x) dx = [(1/2)b² + b + ln I b-1 I ] - [(1/2)a² + a + ln I a -1 I]
a